Whole-Genome Resequencing Identifies KIT New Alleles That Affect Coat Color Phenotypes in Pigs - Wu, Zhongping; Deng, Zheng; Huang, Min; Hou, Yong; Zhang, Hui; Chen, Hao; Ren, Jun (Frontiers in Genetics, 2019)
Duroc × (Landrace × Large White) hybrid pig (DLY) is the most popular commercial pigs in Chinese pig industry. DLY pigs are usually white but sometimes show colored phenotypes. Colored DLY pigs are not favored by slaughterhouses and retailers, thus causing certain economic losses to farmers in China. In this study, we first conducted genome-wide association study and RNA sequencing to demonstrate that KIT variants are responsible for diversifying coat color phenotypes segregating in a DLY population. We then defined the precise sizes and locations of four duplications (DUP1-4), four candidate causative mutations at the KIT locus, in the pig reference genome using the whole-genome sequence data of representative colored individuals. The sequence data also enabled us to identify a list of new KIT alleles. By investigating the association between these new alleles and coat color phenotypes, we provide further evidence that DUP2 is another causative mutation for the solid white coat color in pigs. DUP1 (the KIT gene duplication), DUP2 and the splice mutation are all required for manifestation of solid white coat color. DUP4 had a more significant effect on the formation of the belt phenotype compared with DUP3. Given the necessity of DUP2 for the solid white coat color, we detected IN/IN homozygotes lacking DUP2 in Large White and Landrace pigs and found that French Landrace pigs had the highest frequency (8.98%) of IN/IN individuals. This study not only advances our understanding of the molecular mechanism of the color phenotype in pigs, but also establishes a simple and accurate method for the screening of KIT IN/IN homozygotes in Large White and Landrace that would cause colored DLY pigs.